Innovative method for encapsulating highly pigmented biomass from Aspergillus nidulans mutant for copper ions removal and recovery - Toledo, Ailton Guilherme Rissoni [UNESP]; Andrade, Jazmina Carolina Reyes [UNESP]; Palmieri, Mauricio Cesar; Bevilaqua, Denise [UNESP]; Sponchiado, Sandra Regina Pombeiro [UNESP] (Public Library of Science (PLoS), 2021)
Biosorption has been considered a promising technology for the treatment of industrial effluents containing heavy metals. However, the development of a cost-effective technique for biomass immobilization is essential for successful application of biosorption in industrial processes. In this study, a new method of reversible encapsulation of the highly pigmented biomass from Aspergillus nidulans mutant using semipermeable cellulose membrane was developed and the efficiency of the encapsulated biosorbent in the removal and recovery of copper ions was evaluated. Data analysis showed that the pseudo-second-order model better described copper adsorption by encapsulated biosorbent and a good correlation (r2 > 0.96) to the Langmuir isotherm was obtained. The maximum biosorption capacities for the encapsulated biosorbents were higher (333.5 and 116.1 mg g-1 for EB10 and EB30, respectively) than that for free biomass (92.0 mg g-1). SEM-EDXS and FT-IR analysis revealed that several functional groups on fungal biomass were involved in copper adsorption through ion-exchange mechanism. Sorption/desorption experiments showed that the metal recovery efficiency by encapsulated biosorbent remained constant at approximately 70% during five biosorption/desorption cycles. Therefore, this study demonstrated that the new encapsulation method of the fungal biomass using a semipermeable cellulose membrane is efficient for heavy metal ion removal and recovery from aqueous solutions in multiple adsorption-desorption cycles. In addition, this reversible encapsulation method has great potential for application in the treatment of heavy metal contaminated industrial effluents due to its low cost, the possibility of recovering adsorbed ions and the reuse of biosorbent in consecutive biosorption/desorption cycles with high efficiency of metal removal and recovery.